Telaah Etika Sinematika Deleuze Pada Reprensentasi Perempuan Jawa dalam Film 'SETAN JAWA’ Karya Garin Nugroho - Dewi, Agustina Kusuma; Piliang, Yasraf Amir; Irfansyah, Irfansyah (Universitas Komputer Indonesia, 2019)
Film is a medium of visual communication that plays a role in the dissemination of women's concept discourse in Indonesia, one of which is due to its distinctive characteristics that can last for a long period of time, potentially wider in its dissemination, including also being a mass media hypnotic culture. The film is closely related to the concept of gaze, male gaze in the cinematography industry, which according to overly uses men's views, which is positioning women as subjects who have no power over themselves (self-possessiveness) but as objects of male gaze. Women become commodities in the film, a sex object that is commodified to construct an image that represents the position of women is as an additional role that is not important in one film narrative. In the male gaze narration, women in the film do not act, but become part of the actions of men. Morally, male gaze assumes that the behavior of women in films has a vacuum, but in Garin Nugroho's 'Setan Jawa’ using Deleuze's cinematic study, women are positioned to have other representations that differ from the ethics of cinematics which do not place women as signs of sex objectification for the sake of fulfillment of men's desires, but as subjects who are fully empowered and may wish of themselves.